Experimental Evolution in Coral Photosymbionts as a Tool to Increase Thermal Tolerance - Chakravarti, Leela J.; van Oppen, Madeleine J. H. (Frontiers in Marine Science, 2018)
Coral reefs are under major threat from ocean warming. When temperatures become too high corals bleach, expelling their symbiotic, photosynthetic microalgae (Symbiodinium), which they depend on for much of their nutritional requirements. Prolonged bleaching has led to widespread coral mortality and the severity and frequency of bleaching events are predicted to increase in the future. Coral bleaching tolerance is influenced by the thermal tolerance of the Symbiodinium harboured, and these microbial members of the coral holobiont may be able to evolve more rapidly than the coral host itself. Here, we examined the response of replicate cultures of five genetically distinct Symbiodinium strains (A3c, two types of D1, G3 and F1) to increasing temperatures over the course of approximately one year. For three Symbiodinium types (types A3c, G3 and F1), we observed a stable adaptive change at the end of this exposure period, which equated to only 41-69 asexual generations. The long-term selected Symbiodinium culture replicates (SS) showed faster growth rates under short-term, acute heat stress, and in some cases higher photosynthetic efficiencies, compared to wild-type populations (WT). Our results considerably extend the field of experimental evolution in Symbiodinium and with further work into the Symbiodinium-coral association and bleaching response, this approach may become a valuable tool in coral reef conservation and restoration initiatives.